The Factors that influence OCBE in generation X and generation Y - Ricka Yunita Prasetya; Lenny C Nawangsari; Sutawidjaya, Ahmad hidayat (Technium Social Sciences Journal, 2020)
Organizational Citizenship Behavior for Environment (OCBE) is very important to encourage the achievement of a Green Organization. This study aims to determine the effect of Leadership Style, Organizational Culture and Work Motivation on OCBE in two groups of workers, namely generation X and generation Y. This type of research is a quantitative research with a survey method with a sample of 86 employees in the Directorate General of Fiscal Balance. Analysis of research data using SEM-PLS. The results of this study indicate that Leadership Style, Organizational Culture, and Work Culture have an effect on employee OCBE either directly or simultaneously on generation Y employees but in the group X generation employees it is proven that Organizational Culture has no effect on OCBE.